Essential thrombocythemia as an initial presentation of polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes syndrome with complete response to the bortezomib, cyclophosphamide, dexamethasone regimen: a case report - Alireza Zangooie; Zahra Moradi; Reza Asgari; Amirhosein Maharati; Zahra Salehi; Abolghasem Allahyari (Journal of Medical Case Reports)
Abstract Background Polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes syndrome is a rare paraneoplastic disorder often presenting with atypical manifestations, making diagnosis challenging. This case is novel due to the rare presentation of essential thrombocythemia as the initial manifestation of polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes syndrome. Furthermore, it highlights the remarkable therapeutic response, achieving a complete remission following treatment with the bortezomib, cyclophosphamide, dexamethasone regimen, underscoring this combination therapy’s efficacy in managing such complex cases. Case presentation A 65-year-old Iranian woman presented with fatigue, headache, and thrombocytosis, leading to a diagnosis of essential thrombocythemia. Over time, her condition progressed with the development of neuropathy and persistence of thrombocytosis, which warranted further investigation. Imaging revealed multiple lymphadenopathies, sclerotic bone lesions, and ascitic fluid, raising suspicion for a plasma cell dyscrasia. Bone marrow biopsy, lymph node biopsy, and elevated vascular endothelial growth factor levels confirmed the diagnosis of polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes syndrome. The patient was treated with bortezomib, cyclophosphamide, dexamethasone chemotherapy regimen, resulting in complete symptom relief, normalization of the complete blood count, and significant improvement in imaging findings. Conclusion This case highlights the need to recognize atypical polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes syndrome presentations, such as essential thrombocythemia, for timely diagnosis and underscores the bortezomib, cyclophosphamide, dexamethasone regimen’s efficacy in achieving complete remission.